An urgent call for I-O psychologists to produce timelier technology research. Issue 3 (September 2022) - White, Jerod C.; Ravid, Daniel M.; Siderits, Ian O.; Behrend, Tara S.
Abstract: The rapid pace at which technology changes creates a challenge for industrial-organizational (I-O) psychologists, who often conduct hypothetico-deductive research. In this article, we examine technology research in the I-O psychology community by asking three questions: Why should I-O psychologists study new technologies? How timely is I-O psychologists' technology research? How can I-O psychologists produce timelier technology research? Using archival data from 23 years of SIOP conferences and a historical timeline of technology innovations, we find that I-O psychologists study technology milestones an average of 6.10 years after they first enter widespread awareness and adoption. We discuss the implications of this lag and conclude by urging I-O psychologists to study technology with an eye toward action, exploration, collaboration, dissemination, and creation.